EVALUATION OF FREE RADICAL PROCESSES AND ANTIOXIDANT PROTECTION IN ANIMALS WITH EXPERIMENTAL PERITONITIS AND PROVIDED CERULOPLASMIN CORRECTION - Герасимчук, М. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Despite significant achievements at the surgery, anesthesiology, critical care medicine, pharmacology and other fields of medicine, peritonitis mortality is still very high, and according to various authors ranged from 20% to 92.8%. In this regard, there is very relevant study of the key features of the pathogenesis of acute diffuse peritonitis (ADP) in the context of modern advances in medical and pharmaceutical industry and finding new ways to prevent the development of complications. The object of the study was the blood of 128 white male Wistar rats, which were divided into 4 groups: I – intact, II – control, III – experimental fecal ADP; IV – with ADP and administration of Biotserulin ("Biopharma", Kyiv, Ukraine), former name – Ceruopasmin, 10 mg/kg intraperitoneally once after 30 minutes of the experiment starts. In samples were indicators of lipid peroxidation, diene conjugates (DC) and active products of tiobarbituric acid (TBA-AP). Also evaluated antioxidant state protection (ASP) using catalase activity and ceruloplasmin (CP) at 1, 12, 24 and 48 h of the experiment. Established that ADP accompanied by severe activation of lipid peroxidation with progressive growth of DC and TBA-AP, and the inadequate reaction of the enzyme antioxidant protection. However, under conditions determined by ceruloplasmin correction were significant decrease lipid peroxidation and increased activity of antioxidant protection. In addition, the animals of group IV recorded a significant decrease mortality by 15%.